Menuju Gereja yang Sinodal: Memahami Gagasan Sinodalitas Sebagai Cara Hidup dan Cara Bergerak Gereja di Millenium Ketiga - Hilario Didakus Nenga Nampar (Jurnal Ledalero, 2022)
Abstract: This paper intends to explore the idea of synodality proposed by Pope Francis as the main theme of the XVI Ordinary General Assembly of the Synod of Bishops in 2023. From the results of literature research, the author finds that the idea of synodality, in fact, is not new and does not even have a theological basis. The Holy Trinity and the Eucharist are the two theological foundations of the idea of synodality. So that the theme of synodality does not just stop at an idea and a dream, Pope Francis also provides explains the method and dangers during the synod process. The synod method, which can also be useful for the Church's pastoral method, is meeting, listening, and discernment. The danger in the synod process and the life of the Church is a formalism that is triggered by clericalism, intellectualism, and complacency. From the exploration of the two theological foundations and the discourse of Pope Francis regarding the idea of synodality, the primacy of God in the life of the Church, faith as the basis of true participation in the life of the Church, and mission as a consequence of faith, are three important things that need to be constantly considered so that the idea of synodality can be understood and applied appropriately.Keywords:  Church, Synodality, Pope Francis.